Rekayasa Sosial dalam Mewujudkan Solidaritas Masyarakat Pada Program Kampung Tangguh Semeru di Desa Slemanan, Kabupaten Blitar - Umi Farah Nur Imama; Andika Yudha Pratama (Public Sphere Review, 2023)
Social solidarity is one of the spearheads of handling the pandemic. This value is believed to be able to provide a design for community behavior to build awareness between individuals and groups to jointly share support in facing crisis situations. The patterns that were formed after the implementation of the policy became a valuable inheritance, especially in providing the formation of community solidarity even though the pandemic was at the end of time. Therefore, this is the goal of explaining social engineering to create community solidarity after Kampung Tangguh Semeru in Slemanan Village, Udanawu District, Blitar Regency as well as the role of the multi-stakeholders involved by challenging it in designing Kampung Tangguh Semeru policies so that community social solidarity is created. This study uses a qualitative descriptive research method. Sources of data used in this research are primary data and secondary data. Data analysis used in this study is data reduction, data presentation and conclusions. Furthermore, the data validity technique in this study is by triangulation of sources and techniques. The results of the research that Tangguh Semeru Village is a social engineering that was deliberately made in Slemanan Village to create social solidarity is evidenced by the various Tangguh Semeru Village programs that are still being carried out today, this cannot be separated from the role of the community and stakeholders.